Pengaruh Corporate Social Responsibility, Profitabilitas, Beban Pajak Tangguhan Terhadap Manajemen Laba - Dwi Ermayanti Susilo; Ina Nikmatul Chasanah; Imam Hasan (Politeknik Ganesha Medan, 2025)
This research was conducted to determine the influence of Corporate Social Responsibility, Profitability, Deferred Tax Burden on Profit Management. Deferred tax assets arise if the time difference causes a positive correction so that the tax burden according to accounting is smaller than the tax burden according to tax regulations. Meanwhile, according to the Statement of Financial Accounting Standards (PSAK) No. 46 Revised 2017, deferred tax assets are the amount of income tax recoverable in the future period as a result of temporary differences that may be deducted and remaining loss compensation. Companies always try to reduce the amount of taxable profit with the aim of keeping tax payments low. The research uses quantitative methods with time series data for 2019-2022. The data analysis technique used is multiple linear regression analysis. The source of research data comes from 16 companies in the Automotive Sub Sector on the Indonesia Stock Exchange (BEI). The sampling technique in this research was purposive sampling method, data was obtained from 16 companies. The research results show that Corporate Social Responsibility (CSR) has an effect on Profit Management. Return On Assets (ROA) influences Profit Management. Deferred Tax Expenses affect Profit Management